Seasonal variation in the phenolic content of oak leaves (Quercus sideroxyla) in different soil textures - Arámbula-Salazar, Jorge Armando; Ibarra-Salinas, B. I.; González-Laredo, Rubén Francisco; Muñoz-Galindo, O. D.; Hernández-Vela, H. (Instituto de Ecología, A.C., 2016)
The seasonal variation and the soil texture effect were evaluated in the phenolic contents (FolinCiocalteu) of Quercus sideroxyla ( red oak) leaves as a parameter of the genus deterioration. Leaves of six trees from eight sites were sampled and their edaphic characteristics determined as soil texture: clayed (12,5%), lime-clayed (75%) and clay-sandy (12,5%). Soils and sites were unaltered during the four season collections. It was found in spring a notorious decrease in phenolic content of Quercus leaves followed by a substantial increase during summer. A high positive correlation was found between phenolic content of leaves and electric conductivity of clay-sandy soils, and also between soil moisture retention and phenolic content, independently of the soil texture.